2015
DOI: 10.1186/s40543-015-0070-5
|View full text |Cite
|
Sign up to set email alerts
|

Psychological stress and cancer

Abstract: Psychological or psychosocial stress has been emerging as one of the key factors associated with cancer initiation, growth, and metastasis. Accumulating data, however, has mainly focused on cancer progression due to the inconsistent results of cancer etiology caused by emotional stress. Depression is closely linked to stress and induces hypothalamic-pituitary-adrenal (HPA) axis activation as well as sympathetic nervous system (SNS) down to immune cell surveillance. This review briefly describes the activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 78 publications
1
16
0
2
Order By: Relevance
“…Of the many prolonging psychological impacts of cancer, stress is one associated with its growth and progression. [ 16 ] It is also closely associated with other psychological comorbidities such as anxiety and depression. [ 15 ] Studies have indicated the improvement of patients' prognosis by enhancing their immune system while alleviating stress through psychological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Of the many prolonging psychological impacts of cancer, stress is one associated with its growth and progression. [ 16 ] It is also closely associated with other psychological comorbidities such as anxiety and depression. [ 15 ] Studies have indicated the improvement of patients' prognosis by enhancing their immune system while alleviating stress through psychological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, low socioeconomic status, a known chronic stress factor, is linked to increased cancer incidence for some cancer types, but not all ( Clegg et al, 2009 ). Several potential mechanisms for stress-related cancer induction have been proposed, usually linking stress- and depression related CNS activity to immune responses and HPA-axis regulated hormonal secretion ( Soung and Kim, 2015 ; Shin et al, 2016 ). In support of the proposed links between psychological stress and cancer, a recently published prospective cohort study found that adolescent psychological stress resilience was associated with adult cancer occurrence, even after adjusting for socioeconomic circumstances in childhood, and cognitive and physical fitness ( Kennedy et al, 2017 ).…”
Section: Applying the Model: Neurodegenerative Disease And Cancermentioning
confidence: 99%
“…Stress can alter sleep patterns and lead to behavioral changes that further influence health, such as using drugs or tobacco or using excessive amounts of alcohol or caffeine 22 . Physical illnesses associated with or exacerbated by stress, include asthma, 23 gastroesophageal reflux disease, 24 irritable bowel syndrome, 25 peptic ulcer disease, 26 coronary artery disease, 27 myocardial infarction, 28 and cancer 29 . Chronic stress and psychological distress may also result in physical pain or other illness such as depression and anxiety 30 , 31 .…”
Section: Complex Emergencies and Their Consequences On Health Professmentioning
confidence: 99%